Valorization of shrimp waste by chemical extraction of chitin and chitosan - IHAMOUCHEN, Chadia (Biopolymer Applications Journal, 2025)
The aim of the present work is the recovery of co-products from shrimp shells by isolation of chitin and chitosan. Chitin is the major structural component of the exoskeleton of invertebrates. Chitosan, the deacetylated form of chitin, exhibits many biological activities including antifungal, antibacterial properties, wound-healing properties, and tumor inhibition. Its biological and physico-chemical properties make it an attractive biopolymer for highly targeted applications. The shrimp shells are widely used as raw material to isolate chitin, which is done by, the chemical or enzyme method. In this study, the choice is made on the first method which requires the dissolution of minerals, by acid treatment and extraction of the proteins by a basic treatment, followed by a stage of bleaching to remove pigments. Chitosan, it is obtained by deacetylation of chitin. The isolated substances were characterized by several techniques: chemical characterization, infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and the X-ray diffraction. FTIR analysis confirmed the conversion of chitin to chitosan with deacetylation of 78.7%. The presence of a high crystalline portion in the chitin was observed by XRD. Regarding the glass transition, the estimated humidity 6% of the chemical characterization in chitin played the role of a plasticizer; therefore, there was a decrease in Tg.